Analyzing the Metabolomic Profile of Yellowtail (Seriola quinquerdiata) by Capillary Electrophoresis–Time of Flight Mass Spectrometry to Determine Geographical Origin - Jiyoung Shin; Junho Yang; Eunji Cha; Hyunsuk Kim; Yoonhyeung Lee; Soi Kim; Iseul Choi; Jiyoung Yang (Metabolites, 2021)
Country-of-origin violations have occurred in which some merchants have fraudulently sold cheap Japanese yellowtail (Seriola quinqueradiata) by presenting them as domestic Korean products. There are many methods for determining the origins of marine organisms, such as molecular genetic methods and isotope analysis. However, this study aimed to develop a method for determining the origins of aquatic products using metabolite analysis technology. Ten yellowtail each from Korea and Japan were analyzed by capillary electrophoresis–time of flight/mass spectrometry (CETOF/MS). Hierarchical cluster analysis (HCA) and principal component analysis (PCA) results showed highly differing aspects between the Korean and Japanese samples. In the tricarboxylic acid (TCA) cycle, citric, malic, oxaloglutaric, and fumaric acids exhibited significant differences between Korean and Japanese yellowtail. Sixteen of the twenty essential amino acids analyzed as metabolites also differed significantly. All amino acids were involved in protein digestion, absorption, and metabolism. All 16 amino acid contents were higher in Japanese yellowtail than in Korean yellowtail, except for glutamine. The fasting period was found to be the biggest factor contributing to the difference in amino acid contents, in addition to environmental factors (including feeding habits). These significant differences indicated that metabolomics could be used to determine geographical origin.